Burials of children from Middle to Late Iron Age in south-western Finland : Customs and symbolism - Virtanen, Henna (My University, 2018)
Studies of children have been scarce in archaeology up until the 1990’s in Finland and elsewhere. This was due to the preconception about children as invisible in the archaeological record and thus being non-researchable. This thesis approaches the study of children in the Finnish archaeological record by analysing the graves of children on three Iron Age cemeteries: Luistari in Eura, Kirkkomäki in Turku and Ristimäki at Ravattula in Kaarina. The burial customs of each cemetery are studied and compared to those of adults’ in order to make conclusions about the burial customs concerning children and infants. The samples of children are sorted into hypothetical age groups according to evaluated height measurements and their possible correlations to the grave furnishings are studied. New hypothetical stature estimates for children in the Iron Age are also presented. It is concluded that the number of children under 5-years-old was smaller than could be expected by the estimated mortality rate and the reasons behind this phenomenon are discussed. It is suggested that infants were customarily buried elsewhere. It is also concluded that children were treated in a similar manner compared to each other based on age estimates on all sites, apart from few exceptions, and that no clear differences between the grave-furnishings between children and adults could be found.
Keywords: age groups, burial customs, childhood, children, grave goods, inhumation burials, Iron Age, mortality rates, mortuary archaeology